Atmospheric Bulk Deposition of Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans, and Polychlorinated Biphenyls in Finland - Markku Korhonen; Matti Verta; Simo Salo; Jussi Vuorenmaa; Hannu Kiviranta; Päivi Ruokojärvi (Journal of Marine Science and Engineering, 2016)
The deposition of polychlorinated dibenzo-p-dioxins, dibenzofurans (PCDD/Fs), and polychlorinated biphenyls (PCBs) was studied during the period 2006–2008 in northern Finland (Pallas), 1998–2008 in southern Finland (Evo) and 2002–2004 in the Gulf of Finland archipelago (Utö). Retrospective snow samples were taken from the whole snowbank in Evo in 2003 and 2004, and recently fallen snow was collected in Evo in 2006–2008. The concentrations of PCDD/Fs in the depositions were usually small. The limit of quantification (LOQ) was often reached in Pallas and Utö. The analysis results of PCDD/F and PCB congeners from Evo were used to predict numerical results with linear regression for those congeners with results below LOQ. The deposition of PCDD/Fs in Pallas was mostly less than 0.4 pg·m−2·day−1 WHO-TEQ and less than 1.0 pg·m−2·day−1 WHO-TEQ and 0.5 pg·m−2·day−1 WHO-TEQ in Evo and Utö, respectively. The deposition of co-planar PCBs (cPCBs) was between 0.01 and 0.1 pg·m−2·day−1 WHO-TEQ. Annual PCDD/F deposition, calculated from the amount of collected rain and chemical analysis results, varied in Pallas between 0.04 and 0.15 ng·m−2·year−1 WHO-TEQ, in Evo between 0.11 and 0.22 ng·m−2·year−1 WHO-TEQ and in Utö between 50 and 145 pg·m−2·year−1 WHO-TEQ. For cPCBs the annual deposition in Pallas was 2–11 pg·m−2·year−1 WHO-TEQ, in Evo 6–17 pg·m−2·year−1 WHO-TEQ and in Utö 4–8 pg·m−2·year−1 WHO-TEQ. Wind directions are considered to be the main reason for the variation between seasons. Congener 1,2,3,7,8-PeCDD dominated in Pallas, Evo, and Utö, being 35%, 48%, and 47% of the overall WHO-TEQ, followed by 2,3,4,7,8-PeCDF (about 10%). The calculated pg/L concentrations of 1,2,3,7,8-PeCDD were about the same level as 2,3,4,7,8-PeCDF, but the TEF correlations being twice as big ensured that all WHO-TEQ contributions were bigger. PCB126 accounted for 30% of WHO-TEQ in Pallas, whereas in Evo and Utö the proportion was less than 5%. Of PCDD/F homology groups, the highest concentration was found in Pallas as OCDDs (55%), followed by ...